A self-determination theory based investigation of life skills development in youth sport - Cronin, L.; Ellison, P.; Allen, J.; Huntley, E.; Johnson, L.; Kosteli, M. C.; Hollis, A.; Marchant, D. (Journal of Sports Sciences, 2022)
This study investigated if basic need satisfaction and frustration mediated the associations between autonomy-supportive and controlling coaching behaviours and participants` development of eight different life skills in youth sport. British sports participants (N = 309, Mage = 14.71) completed measures assessing the study variables. Correlational analyses showed that autonomy-supportive coaching behaviours were positively associated with the satisfaction of participants` three basic needs (autonomy, competence, and relatedness) and their development of all eight life skills, whereas controlling coaching behaviours were only positively related to the frustration of participants` three basic needs. Mediational analyses revealed that satisfaction of all three basic needs combined (total need satisfaction) mediated the associations between autonomy-supportive coaching behaviours and participants` development of the eight life skills. Relatedness satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants` development of all eight life skills except for goal setting; autonomy satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants` time management skills; and competence satisfaction mediated the associations between autonomy-supportive coaching behaviours and participants` goal setting and emotional skills. Based on such findings, coaches should look to display autonomy-supportive behaviours that help to satisfy participants` three basic psychological needs and promote their life skills development in sport.